2020
DOI: 10.3390/ijms21051713
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Lysosomal Positioning and Small Extracellular Vesicle Secretion in Arterial Stiffening and Calcification of Mice Lacking Mucolipin 1 Gene

Abstract: Recent studies have shown that arterial medial calcification is mediated by abnormal release of exosomes/small extracellular vesicles from vascular smooth muscle cells (VSMCs) and that small extracellular vesicle (sEV) secretion from cells is associated with lysosome activity. The present study was designed to investigate whether lysosomal expression of mucolipin-1, a product of the mouse Mcoln1 gene, contributes to lysosomal positioning and sEV secretion, thereby leading to arterial medial calcification (AMC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…However, lysosomal function was also shown to promote VCN by degrading the anti-calcifying protein granzyme B. Knocking out Mcoln1 enhanced VCN both, in vivo and in vitro by impairing lysosomal trafficking, and consequentially enhancing secretion of pro-calcific small extracellular vesicles (sEVs) ( Table 1 ) [ 79 ]. Asah1 gene deletion also aggravated VCN and decreased TRPML1 activity, leading to impaired lysosomal trafficking and enhanced pro-calcific sEV secretion [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lysosomal function was also shown to promote VCN by degrading the anti-calcifying protein granzyme B. Knocking out Mcoln1 enhanced VCN both, in vivo and in vitro by impairing lysosomal trafficking, and consequentially enhancing secretion of pro-calcific small extracellular vesicles (sEVs) ( Table 1 ) [ 79 ]. Asah1 gene deletion also aggravated VCN and decreased TRPML1 activity, leading to impaired lysosomal trafficking and enhanced pro-calcific sEV secretion [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Knocking-out Mcoln1 , which is the gene that encodes TRPML1, resulted in increased VCN both in vitro and in vivo. Moreover, increased secretion of pro-calcific sEVs was reported in the absence of TRPML1 [ 79 ]. sEVs contain a variety of cargoes such as proteins and lipids that can chelate Pi and calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary evidence also demonstrated the vitamin D might stimulate vascular calcification by modulating the expression of parathyroid hormone-related peptide or the receptor activator of nuclear factor kappa-B ligand/osteoprotegerin of VSMC [42,43]. The pharmacologic or the supraphysiologic concentrations of active or nutritional vitamin D might contribute to the vascular calcification in vivo studies [44,45]. Therefore, vitamin D has rather complex effects on calcification from the aspect of VSMC, and more advanced studies are needed to elucidate the role of vitamin D in vascular calcification.…”
Section: The Role Of Vascular Smooth Muscle Ccells (Vsmcs) In Vasculamentioning
confidence: 98%
“…They found that PWV was significantly increased with age in these mice [ 57 ]. PWV was also found to be increased dramatically in Mcoln1 -/- mice compared to their wild-type littermates, and Vitamin D treatment further enhanced such stiffening in these mice [ 11 ].…”
Section: Integrating Applications Of Ultrasonography In the Assessmentioning
confidence: 99%
“…It is also known as an independent risk factor of cardiovascular complications and has been considered as a predictor of cardiovascular outcomes in clinical [ 8 , 9 , 10 ]. As a non-invasive method, ultrasonography has been used in clinical diagnosis for aortic stiffness in many aortic disorders such as atherosclerotic degeneration and aortic aneurysms through measuring the wall-thickness, diameter, structural defects, blood flow velocity, and other pathological changes in the aorta [ 7 , 11 , 12 , 13 ]. The developed techniques used in patients also provide powerful tools for basic science research in different animal models, particularly the large animal models such as monkeys, swine, canines, and horses [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%